MANAJEMEN STRATEGIK DENGAN PENDEKATAN BALANCED SCORECARD DI IAIN SYEKH NURJATI DALAM UPAYA TRANSFORMASI MENJADI UIN - Kurniawan, Asep; Sumadi, Sumadi (LP2M IAIN Syekh Nurjati Cirebon, 2016)
The transformation of IAIN Sheikh Nurjati to a university is an inevitability. This is due to the tendency of the educational market which increasingly leaves